Learning Difficulties in Computing Courses: Cognitive Processes Assessment Methods Research and Application - Pessoni, Vinicius; Federson, Fernando; Vincenzi, Auri (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2015: Anais do XI Simpósio Brasileiro de Sistemas de Informação, 2015)
Learning difficulties in computing courses is a situation perceived in diverse universities from different countries, cultures and backgrounds. These difficulties directly affect achievement rates and increase course evasion. We believe in the existence of a foundation of cognitive processes, that without it, even the most motivated student would have trouble to transform the received information into knowledge. This work has focused mainly on the research of candidate methods for cognitive processes assessment with a strong background theory. With this kind of information would be possible to devise cognitive interventions, in order to evolve students cognitive level, and consequently, raise their success rates. A systematic review was conducted and among the many researched methods we selected Lawson Classroom Test of Scientific Reasoning – LCTSR. Authorized by its author, we conducted the first translation of LCTSR to Brazilian Portuguese and administered to students of three undergraduate computing courses: Information Systems, Computer Science and Software Engineering. We also present results of its administration that we consider important to reinforce the above suggested strategy.